INTRAMURAL AEROMYCOLOGICAL STUDY OF GOVERNMENT ADIWASI GIRLS HOSTEL OF DESAIGANJ WADSA, DISTRICT-GADCHIROLI MAHARASHTRA - SHANKARG.KUKREJA,; DHANSHRI R. BANGALKAR,; ARVIND J. MUNGOLE, (The Bioscan, 2025)
This study investigates the Intramural aeromycoflora of Government Adiwasi girlshostel of DesaiganjWadsa located in Gadchiroli District of Maharashtra state. The sampling was conducted from the different section of hostel, such as Girls room, Dining area, Kitchen. Air samples collected during February, 2023 to January, 2024 for a year at an interval of 15 days. Air sampling was done by two methods with the help of Hi Air Sampler (Mark ll), Hi Media Loboratories, India and simultaneous Exposure Petri plate method. For this study culture media Czapek’s Dox Agar (CDA) was utilized for Petri plate method and Rose Bengal Strips were used in air sampler. Fungal spores were collected from indoor air of different sections of hostel. Total 1312colonies were appeared from Feb-2023 to Jan-2024 by exposure petri plate method. Total6700 CFUs/m3were trapped by sampler method. The genera like Aspergillus, Alternaria, Cladosporium, Penicillium, Fusarium, Mucor, and Rhizopuswere reported in Adiwasi girl’s hostel. Seasonal variations revealed, higher fungal spore concentration and CFUs/m 3 during rainy season correlating with increased humidity and decreased temperature levels. Temperature, Humidity and Rainfall affect the growth of fungus.